Clinical case of caseous lymphadenitis in a goat: case management - Abdullah, Faez Firdaus Jesse; Abba, Yusuf; S. R., Nurul; Adamu, Lawan; Bitrus, Asinamai Athliamai; Lim, Eric Teik Chung; Sadiq, Muhammad Abubakar; Hambali, Idris Umar; Haron, Abd Wahid; Mohd Lila, Mohd Azmi (Department of Veterinary Services Malaysia, 2017)
Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis (CLA) a contagious and infectious disease in small ruminants. This report describes a case of CLA in a Boer cross goat infected with Corynebacterium pseudotuberculosis. The manifestation of abscess in the superficial lymph node presented as a mass of approximately 5cm by 5cm in diameter at the base of the ear. The mass was solid and non-movable upon palpation. The mass was incised and the caseous material was aspirated and sent to the bacteriology laboratory where Corynebacterium pseudotuberculosis was isolated. The wound was cleaned and flushed with diluted chlorhexidine and iodine solutions daily. This procedure aids in the complete healing of the wound after a few weeks. However, the agent of the disease persists in the animal in its entire life and culling is recommended to prevent the spread of the disease in the herd.